ASPECTS OF DEMAND FORMATION STUDENT EXPRESSION IN THE FUTURE PROFESSIONAL ACTIVITY - Annyuk, E.A. (Pedagogy of Higher and Secondary Education, 2006)
The article is devoted to some aspects of formation of students’ needs o f self-expression in the future professional activity in the modern system of personality-oriented education.